Pemberdayaan SDM Kelompok Tani dalam Pengolahan Keong Mas menjadi Pakan Ternak - Syamsir Syamsir; Karjuni Dt. Maani; Jumiati Jumiati (Journal of Education on Social Science (JESS), 2019)
This article (study) was summarized based on writer experiences in conducting Community Service program among farmer group organizations in Anduriang Village at Padang Pariaman Regency. This program was intended to increase the understanding and awareness of farmer groups about the benefits of golden snails, which so far have only been seen as crop pests for farmers, and then made them a source of income. This study was inspired by various conditions that indicated the powerless of the farmer groups in overcoming the problem of golden snail pests in the Anduriang Village at Padang Pariaman Regency. This issue was reflected in part from the lack of understanding and awareness of farmers in controlling the golden snail pests. Based on this condition, various farmer empowerment policies and programs were needed to be implemented in the form of increasing the capacity of the parmers in economic development of the society, especially for the farmer group organization as target groups in this program. These empowerment activities and programs needed to be conducted collaboratively and synergistically between the local government and universities.